Deep learning for detecting visually impaired cataracts using fundus images - Xie, He; Li, Zhongwen; Wu, Chengchao; Zhao, Yitian; Lin, Chengmin; Wang, Zhouqian; Wang, Chenxi; Gu, Qinyi; Wang, Minye; Zheng, Qinxiang; Jiang, Jiewei; Chen, Wei (Frontiers in Cell and Developmental Biology, 2023)
Purpose: To develop a visual function-based deep learning system (DLS) using fundus images to screen for visually impaired cataracts.A total of 8,395 fundus images (5,245 subjects) with corresponding visual function parameters collected from 3 clinical centers were used to develop and evaluate a DLS for classifying noncataracts, mild cataracts, and visually impaired cataracts. Three deep learning algorithms (DenseNet121, Inception V3, and ResNet50) were leveraged to train models to obtain the best one for the system. The performance of the system was evaluated using the area under the receiver operating characteristic curve (AUC), sensitivity, and specificity.The AUC of the best algorithm (DenseNet121) on the internal test dataset and the two external test datasets were 0.998 (95% CI, 0.996-0.999) to 0.999 (95% CI, 0.998-1.000),0.938 (95% CI, 0.924-0.951) to 0.966 (95% CI, 0.946-0.983) and 0.937 (95% CI, 0.918-0.953) to 0.977 (95% CI, 0.962-0.989), respectively. In the comparison between the system and cataract specialists, better performance was observed in the system for detecting visually impaired cataracts (P < 0.05).Our study shows the potential of a function-focused screening tool to identify visually impaired cataracts from fundus images, enabling timely patient referral to tertiary eye hospitals.Deep learning system ROC Receiver operating characteristic curve